1991
DOI: 10.1085/jgp.98.4.723
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of an epithelial chloride channel. Conservation of the channel from mudpuppy to man.

Abstract: We have previously shown that monoclonal antibody El2 (MAb E12), one of several such antibodies raised against theophylline-treated Necturus gallbladder (NGB) epithelial cells, inhibits the chloride conductance in the apical membrane of that tissue. Since chloride channels are critical to the secretory function of epithelia in many different animals, we have used this antibody to determine whether the channels are conserved, and in an immunoaffinity column to isolate the channel protein. We now demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
(56 reference statements)
0
10
1
Order By: Relevance
“…The opposite effect, namely, disappearance of C1-channel rectification by dephosphorylation, has been observed in A6 cells (Marunaka and Eaton, 1990). The ~ 62-pS channel purified by Finn and co-workers (Finn et al, 1989;Tsai et al, 1991) was never observed in our patch-clamp experiments.…”
Section: Other Anion Channels In the Apical Membrane Of Necturus Gallcontrasting
confidence: 48%
“…The opposite effect, namely, disappearance of C1-channel rectification by dephosphorylation, has been observed in A6 cells (Marunaka and Eaton, 1990). The ~ 62-pS channel purified by Finn and co-workers (Finn et al, 1989;Tsai et al, 1991) was never observed in our patch-clamp experiments.…”
Section: Other Anion Channels In the Apical Membrane Of Necturus Gallcontrasting
confidence: 48%
“…We have previously shown that mAb E12 blocks all cAMP-dependent current in mudpuppy and toad gallbladder, rat colon, cultured human nasal epithelial cells, 6 and mouse colon (Finn AL, unpublished observations), suggesting that this chloride channel is also quite abundant. Indeed, in the mudpuppy gallbladder, this channel must make up a sizable fraction of total apical membrane protein because an increase in cellular cAMP can increase total membrane conductance up to 200-fold, all of which is caused by the appearance of a chloride current that is fully blocked by mAb E12.…”
Section: Discussionmentioning
confidence: 94%
“…6 -8 These channels have identical kinetic characteristics despite a 5-10-fold dilution of the protein, reducing the likelihood that an undetectable impurity might be the channel molecule. Second, the channel is blocked by the antibody, whether it is reconstituted in lipid bilayers 6,8 or expressed in Xenopus oocytes, whereas CFTR channels are not blocked by the antibody. It is also unlikely that the expression of SI in the heterologous systems described above could be accounted for by "piggybacking" of another protein on SI because at least 2 major characteristics of the expression seen in Figures 3 and 4 (the requirement of phosphorylation and the blockade by mAb E12) are similar to those seen in the bilayer expression system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations